2017
DOI: 10.2147/ce.s109654
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin in the treatment of type 2 diabetes: an evidence-based review of its place in therapy

Abstract: IntroductionDeciding on an optimal medication choice for type 2 diabetes is often challenging, due to the increasing number of treatment options. Canagliflozin is a novel glucose-lowering agent belonging to sodium–glucose co-transporter 2 (SGLT2) inhibitors.AimThe aim of this study was to examine and summarize the evidence based on the efficacy, safety, and cost-effectiveness of canagliflozin for type 2 diabetes.Evidence reviewCompared to placebo, canagliflozin 100 and 300 mg lower glycated hemoglobin (HbA1c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Furthermore, in this study, the number of insulin units could be markedly reduced, suggesting the blood glucose-lowering effects of canagliflozin cover a decrease in the dose of insulin. In addition, it was considered to be cost-effective [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, the number of insulin units could be markedly reduced, suggesting the blood glucose-lowering effects of canagliflozin cover a decrease in the dose of insulin. In addition, it was considered to be cost-effective [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in 3P-MACE for a composite score came out lower than the EMPA-REG trial, though the participants in both the trials received statins or lipid-lowering medication, antiplatelet, and renin-angiotensin-aldosterone inhibitors (RAASi) [ 7 ]. A meta-analysis of six RCTs assessed the efficacy of canagliflozin along with metformin monotherapy and was found that administration of canagliflozin reduces HbA1c [ 19 ], but it was found to be associated with an increased risk of below-knee amputation as compared to the placebo. Thus, it is imperative to assess the patients thoroughly before giving the drug [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similar to the EMPA-REG-OUTCOME trial, various other clinical trials have been carried out among different populations and by administering different types of SGLT2i and have reported cardioprotective effects of these anti-diabetic drugs [ 15 - 17 ]. Moreover, the first renal outcome trial on SGLT2i has reported positive renal and CV benefits as well [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several SGLT2 inhibitors, such as empagliflozin [20], canagliflozin [21], and dapagliflozin [22], have been clinically used as antidiabetic drugs. Numerous reports have provided evidence to support their usefulness in reducing hyperglycemia by increasing urinary glucose excretion, both in nonclinical animal models [1823] and in patients with type 2 diabetes [1124].…”
Section: Discussionmentioning
confidence: 99%